2022
DOI: 10.3390/cancers14184411
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nectin-4 in Variant Histologies of Bladder Cancer and Its Prognostic Value—Need for Biomarker Testing in High-Risk Patients?

Abstract: Variant histologies of bladder cancer (BC) often present with advanced tumor stage and the status of perioperative therapy is unclear. Thereby, squamous cell carcinoma (SCC), adenocarcinoma (ADENO), and sarcomatoid urothelial carcinoma (SARCO) are the most frequent variants. Nectin-4 has emerged as a highly interesting target in BC and might guide therapeutic application of antibody–drug conjugates (ADC). We therefore aimed to investigate expression patterns and prognostic value of Nectin-4 in variant histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Studies have highlighted the heterogeneity in nectin‐4 expression within urothelial cancer, noting a decreased positive rate in muscle‐invasive carcinoma compared with non‐muscle‐invasive carcinoma 10 . Another study reported that variations in nectin‐4 expression rates in different variants of urothelial cancer, with squamous cell carcinoma and adenocarcinoma exhibiting a high positive rate, while sarcomatoid urothelial cancer rarely expresses nectin‐4 11 . Furthermore, it has been reported that nectin‐4 expression is reduced in metastatic lesions compared to primary tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted the heterogeneity in nectin‐4 expression within urothelial cancer, noting a decreased positive rate in muscle‐invasive carcinoma compared with non‐muscle‐invasive carcinoma 10 . Another study reported that variations in nectin‐4 expression rates in different variants of urothelial cancer, with squamous cell carcinoma and adenocarcinoma exhibiting a high positive rate, while sarcomatoid urothelial cancer rarely expresses nectin‐4 11 . Furthermore, it has been reported that nectin‐4 expression is reduced in metastatic lesions compared to primary tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
“… 10 Another study reported that variations in nectin‐4 expression rates in different variants of urothelial cancer, with squamous cell carcinoma and adenocarcinoma exhibiting a high positive rate, while sarcomatoid urothelial cancer rarely expresses nectin‐4. 11 Furthermore, it has been reported that nectin‐4 expression is reduced in metastatic lesions compared to primary tumors. 12 These findings underscore the importance of assessing nectin‐4 expression, either in the primary or metastatic lesions, before initiating EV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In Fan et al's immunohistochemical analysis of 161 surgical specimens stained for nectin-4 [24], membranous positive expression was observed in 79.2%, 100%, 65.2%, 21.1%, 78.9%, and 88.9% of conventional UC, squamous, glandular, neuroendocrine differentiation, micropapillary, and nested subtypes, respectively. Moreover, a single-center retrospective analysis on radical cystectomy for SUC showed that sarcomatoid subtypes had low nectin-4 expression [25]. In 2023, Ghali et al reported the prominent cytoplasmic staining of nectin-4 by a rapid autopsy study [26].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity of P2XRs was scored using the histochemical scoring system (H-score) as previously described [ 30 ]. The H-score incorporates both the staining intensity and the percentage of stained cells at each intensity level.…”
Section: Methodsmentioning
confidence: 99%